2014
DOI: 10.1089/bfm.2013.0118
|View full text |Cite
|
Sign up to set email alerts
|

Is Breastfeeding Protective for Blood Pressure in Schoolchildren? A Cohort Study in Northeast Brazil

Abstract: Objective: This study assessed the influence of breastfeeding and nutritional status of full-term infants on blood pressure at school age. Subjects and Methods: This was a cross-sectional study nested in a cohort of 375 infants recruited at birth between 1993 and 1994 in the state of Pernambuco, Brazil. A sample of 213 8-year-old children had their blood pressure measured. A multivariate linear regression analysis was used to identify the influence of low birth weight and breastfeeding duration on blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
2
13
1
Order By: Relevance
“…Likewise, our findings regarding DBP are in general agreement with studies that reported a significant positive association between birth weight and childhood DBP in the unadjusted analysis 29,66 that became nonsignificant (but remained positive) after adjusting for the child's current BMI. 33 Azadbakht and collegues also found significant positive bivariate association between birth weight and DBP as observed in our study. However, in contrast to our findings, this positive association remained statistically significant after adjusting for the child's current BMI in both this 9 and other previous studies.…”
Section: Blood Pressuresupporting
confidence: 89%
See 2 more Smart Citations
“…Likewise, our findings regarding DBP are in general agreement with studies that reported a significant positive association between birth weight and childhood DBP in the unadjusted analysis 29,66 that became nonsignificant (but remained positive) after adjusting for the child's current BMI. 33 Azadbakht and collegues also found significant positive bivariate association between birth weight and DBP as observed in our study. However, in contrast to our findings, this positive association remained statistically significant after adjusting for the child's current BMI in both this 9 and other previous studies.…”
Section: Blood Pressuresupporting
confidence: 89%
“…In addition, due to the unique population characteristics of WV, a predominantly Caucasian rural state entirely within the Appalachian region of the US, results may not be generalizable to other populations, although previous studies have yielded similar findings. 9,28,29,31,33,36,39,66 Lastly, the magnitude of association seems extremely small though statistically significant (small p-values) perhaps due to the large sample size, cautions us about the clinical and population health importance of this association. However, the occurrence of CVD risk factor in childhood is an important concern as these risk factors persist, track, and amplify with age, leading to potentially serious CVDs in later adulthood.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research examining the associations between breastfeeding and later childhood CVD risk factors has yielded conflicting results. For example, while some studies have found a significant protective effect of breastfeeding on child CVD risk factors such as systolic blood pressure (SBP) (Amorim Rde et al 2014;Hosaka et al 2013;Lawlor et al 2004), diastolic blood pressure (DBP) (Martin et al , 2004Owen et al 2003), and lipid levels in childhood (Plagemann and Harder 2005;Plancoulaine et al 2000;Thorsdottir et al 2003), others have not (Bekkers et al 2011;de Jonge et al 2010;Fall et al 2011;Horta et al , 2015Izadi et al 2013;Kramer 2010;Kramer et al 2007;Kwok et al 2013;Owen et al 2002Owen et al , 2008Rudnicka et al 2007). These discrepancies may in part reflect the role of childhood adiposity, a factor associated with blood pressure and cholesterol (McMurray et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies may in part reflect the role of childhood adiposity, a factor associated with blood pressure and cholesterol (McMurray et al 1995). Some studies that did adjust for childhood obesity found that the association between breastfeeding and childhood CVD risk factors became non-significant in the adjusted models (Bekkers et al 2011), whereas others found that even after controlling for body mass index (BMI) the association attenuated but remained statistically significant (Amorim Rde et al 2014;Lawlor et al 2004;Martin et al 2004). These conflicting results suggest that childhood obesity could potentially be a partial or full mediator between the observed effects.…”
Section: Introductionmentioning
confidence: 99%